2
$\begingroup$

Find $$\lim_{x\to +\infty}x\sqrt{x^2+1}-x(1+x^3)^{1/3}.$$

I have tried rationalizing but there is no pattern that I can observe.

Edit:

So we forget about the $x$ that is multiplied to both the functions and try to work with the expression $(x^2+1)^{1/2}-(x^3+1)^{1/3}.$ Thus we have, $$(x^2+1)^{1/2}-(x^3+1)^{1/3}=\frac{((x^2+1)^{1/2}-(x^3+1)^{1/3})((x^2+1)^{1/2}+(x^3+1)^{1/3})}{(x^2+1)^{1/2}+(x^3+1)^{1/3}}$$

$$=\frac{x^2+1-(x^3+1)^{2/3}}{(x^2+1)^{1/2}+(x^3+1)^{1/3}}=\frac{(x^2+1)^2-(x^3+1)^{4/3}}{(x^2+1)^{3/2}+(x^2+1)(x^3+1)^{1/3}+x^3+1+(x^3+1)^{2/3}(x^2+1)}=??$$

$\endgroup$
  • $\begingroup$ Just a thought - how about making the change of variables $w = \frac{1}{x}$ and using the binomial series on the resulting limit of $w$ tending to 0 for the expression $\frac{1}{w^2} ((1+w^2)^{\frac{1}{2}} - (1+w^3)^{\frac{1}{3}})?$ [I am not suggesting that this is an answer; I just want to know if my thinking here is correct.] $\endgroup$ – SystematicDisintegration Dec 12 '17 at 0:57
  • 1
    $\begingroup$ Try the appropriate conjugate for $6$th powers. Hint: factor $x^6-y^6$. $\endgroup$ – Michael Burr Dec 12 '17 at 1:09
4
$\begingroup$

You can do it with Taylor expansions:

$x\left(1+x^{2}\right)^{1/2}-x\left(1+x^{3}\right)^{1/3}= x^{2}\left(1+\frac{1}{x^{2}}\right)^{1/2}-x^{2}\left(1+\frac{1}{x^{3}}\right)^{1/3} =x^{2}\left(1+\frac{1}{2}\cdot\frac{1}{x^{2}}+o\left(\frac{1}{x^{2}}\right)\right)-x^{2}\left(1+\frac{1}{3}\cdot\frac{1}{x^{3}}+o\left(\frac{1}{x^{3}}\right)\right) =\frac{1}{2}-\frac{1}{3x}+o\left(1\right) \to\frac{1}{2}$

$\endgroup$
  • $\begingroup$ I guess the approach I posted as a comment was right then...just a couple of seconds late though! $\endgroup$ – SystematicDisintegration Dec 12 '17 at 0:59
3
$\begingroup$

I like the Taylor expansion approach, but wondered if there was a more "Cal I" approach.

Using $$ A-B = (A^{1/6} - B^{1/6})(A^{5/6} + A^{4/6}B^{1/6} + A^{3/6}B^{2/6} + \cdots + B^{5/6}) $$ with $A = (x^2+1)^3$ and $B = (1+x^3)^2$ gives $$ \begin{multline*} (x^2+1)^{1/2} - (x^3+1)^{1/3}\\ =\frac{(x^2+1)^3 - (x^3+1)^2}{(x^2+1)^{5/2}+ (x^2+1)^{2}(1+x^3)^{1/3} + \cdots + (1+x^3)^{5/3}}\\ =\frac{3x^4+2x^3+3x^2}{(x^2+1)^{5/2}+ (x^2+1)^{2}(1+x^3)^{1/3} + \cdots + (1+x^3)^{5/3}} \end{multline*} $$ Now $$ \begin{multline*} x((x^2+1)^{1/2} - (x^3+1)^{1/3})\\ =\frac{x^5(3+2/x+3/x^2)}{x^5((1+1/x^2)^{5/2}+ (1+1/x^2)^{2}(1+1/x^3)^{1/3} + \cdots + (1+1/x^3)^{5/3})}\\ \end{multline*} $$

which goes to $3/6$ as $x\to \infty$.

$\endgroup$
  • 1
    $\begingroup$ And $3/6$ approaches $1/2$ quite quickly.... $\endgroup$ – CiaPan Dec 12 '17 at 8:14
  • $\begingroup$ @CiaPan :-) ... $\endgroup$ – Malcolm Dec 12 '17 at 8:25
2
$\begingroup$

Let's put $x=1/t$ so that $t\to 0^{+}$ and the expression under limit is transformed into $$\frac{\sqrt{1+1/t^{2}}-\sqrt[3]{1+1/t^{3}}}{t}=\frac{\sqrt{1+t^{2}}-\sqrt[3]{1+t^{3}}}{t^{2}}$$ and this can be expressed as a difference of two standard limits $$\lim_{t\to 0^{+}}\frac{(1+t^{2})^{1/2}-1}{t^{2}}-t\cdot \frac{(1+t^{3})^{1/3}-1}{t^{3}}$$ which equals $1/2-0(1/3)=1/2$. The standard limit formula $$\lim_{x\to 0}\frac{(1+x)^{n}-1}{x}=n$$ used above is a direct consequence of the more general limit formula $$\lim_{x\to a} \frac{x^n-a^n} {x-a} =na^{n-1}$$

$\endgroup$
1
$\begingroup$

Hint: Your expression equals

$$x^2[(1+1/x^2)^{1/2} - (1+1/x^3)^{1/3}].$$

Now use the fact that $(1+h)^p = 1 + ph +o(h)$ as $h\to 0.$ (This fact is equivalent to the statement that the derivative of $(1+x)^p$ at $x=1$ is $p.$)

$\endgroup$
1
$\begingroup$

This limit would be equal to $1/2$. See my demo :
$$ \lim_{x \to \infty} {x\sqrt{x^2+1}-x (x^3+1)^{1/3}} = \lim_{x \to \infty} { x (\sqrt{x^2+1}-(x^3+1)^{1/3})} $$ Now, let us see how much is each member, by Laurent-Taylor expansion : $$ \sqrt{x^2+1} = x+ {1 \over {2x}} - {1 \over {8x^3}}+{1 \over {16x^5}}-... $$ $$ (x^3+1)^{1/3} = x+ {1 \over {3x^2}} - {1 \over {9x^5}}+{5 \over {81x^8}}-... $$ Resting this 2 members : $$ \sqrt{x^2+1}-(x^3+1)^{1/3} = {1 \over {2x}}-{1 \over {3x^2}} - {1 \over {8x^3}}+({1 \over 16}+{1 \over 9}){1 \over x^5}-... $$ Now we substitute this in our limit : $$ \lim_{x \to \infty} { x (\sqrt{x^2+1}-(x^3+1)^{1/3})} = \lim_{x \to \infty} { x ({1 \over {2x}}-{1 \over {3x^2}}-...)}= {1 \over 2} $$

$\endgroup$
  • 1
    $\begingroup$ The opening line did not match the answer at the end. I have taken the liberty to fix it. $\endgroup$ – Paramanand Singh Dec 12 '17 at 3:55

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.